KAIDAH DASAR MANAJEMEN PENDIDIKAN ISLAM MENURUT PERSPEKTIF QUR’AN DAN HADITS - Sri Putrianingsih; Putra, Thoha (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2024)
The Holy Qur'an contains everything related to the existence and dynamics of human life as creatures in the universe. Including the discussion of the history of the origin of human creation by the creator to the activities carried out by humans. One of them is about education management. In this case because the holy book al quranul karim is the main teaching of Islam whose function is as a guide for mankind so that mankind becomes a good and right "khalifatun fil ardhi". In studying the principles of management, a more in-depth study of the content of the Qur'an is needed as an effort for mankind to get guidance, so that Muslims can really benefit and apply according to the guidance in the Qur'an. The content of the Holy Qur'an is very complex, it contains various kinds of problems that have occurred, current events, even future events or those that will occur in the future. It has been written in the verse of the Qur'an problems in the realm of education management as well as those found in the hadith. What is explained in the hadith is the basic principle of Islamic teaching second only to the holy book Al-Qur'an. Hadith becomes a second foundation in the principle of Islamic education management. This is because the hadith provides a comprehensive explanation of the holy Quran.